PENGARUH METACOGNITION, MOTIVATION, DAN BEHAVIOR TERHADAP KINERJA MAHASISWA SELAMA PERKULIAHAN DARING: STUDI KASUS PADA MAHASISWA AKUNTANSI UNIVERSITAS TRILOGI - Noviola, Anisha; Ludwina Harahap (RELEVAN : Jurnal Riset Akuntansi, 2024)
This study investigates the impact of metacognition, motivation, and behavior on the performance of accounting students during online learning at Universitas Trilogi Jakarta amidst the COVID-19 pandemic. The subjects of this research were accounting students at trilogi university. Primary data were collected through a questionnaire distributed via Google Forms. The sampling technique used was purposive sampling with the Slovin formula and a precision level of 10%, with a sample size of 80 respondents. The analysis was conducted using Structural Equation Modeling (SEM) with the assistance of Partial Least Squares (PLS) for data interpretation. The findings indicate that metacognition and motivation do not significantly affect the performance of accounting students at Universitas Trilogi, while the behavior variable shows that they have a positive influence on the performance of accounting students at Trilogy University, so it can be said that accounting students at Trilogy University have good behavior or behavior patterns that can affect academic performance.